PELIGROSIDAD, ALGORITMOS Y DUE PROCESS: EL CASO STATE vs. LOOMIS - Martínez Garay, Lucía (2020)
The contemporary tendency towards replacing the old notion of dangerousness by the risk assessment approach, that began in the correctional settings, is reaching other stages of the criminal justice, particularly the sentencing phase. Presenting itself as an evidence-based practice (evidence-based sentencing), it promotes introducing structured risk assessments in sentencing in order to help the judge impose the penalty that best prevents recidivism. This paper critically examines one of the first State Supreme Court decisions in the USA that has had to face the problems posed by this approach, and especially the following: is it compatible with due process rights to impose an enhanced sentence based on the risk assessment made by a secret algorithm, the details of which are not disclosed to the defendant due to its proprietary nature?El movimiento contemporáneo tendente a la sustitución de la noción de peligrosidad por el enfoque de la valoración del riesgo (risk assessment), que se inició en el ámbito del derecho penitenciario y de ejecución de las penas, está llegando a otras fases del proceso penal, como la de sentencia. Presentándose como una práctica «basada en la evidencia» (evidence-based sentencing), propugna tomar en consideración las valoraciones estructuradas del riesgo de reincidencia a la hora de determinar la clase y cuantía de la pena a imponer, para adecuarla mejor a las necesidades de prevención especial. El presente trabajo analiza críticamente una de las primeras sentencias de un tribunal supremo estatal de los EEUU que se ha enfrentado a los problemas que plantea esta propuesta, y en particular al siguiente: ¿es compatible con el derecho al debido proceso agravar la pena sobre la base de la valoración de riesgo hecha por un algoritmo, cuyo funcionamiento no se desvela al acusado porque está protegido como secreto de empresa?The contemporary tendency towards replacing the old notion of dangerousness by the risk assessment approach, that began in the correctional settings, is reaching other stages of the criminal justice, particularly the sentencing phase. Presenting itself as an evidence-based practice (evidence-based sentencing), it promotes introducing structured risk assessments in sentencing in order to help the judge impose the penalty that best prevents recidivism. This paper critically examines one of the first State Supreme Court decisions in the USA that has had to face the problems posed by this approach, and especially the following: is it compatible with due process rights to impose an enhanced sentence based on the risk assessment made by a secret algorithm, the details of which are not disclosed to the defendant due to its proprietary nature